2019
DOI: 10.17584/rcch.2019v13i1.7967
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between morpho-agronomic traits in tomato hybrids

Abstract: The objective of this study was to identify and estimate the relationships between production component variables and fruit yields in tomatoes. This experiment was conducted in a randomized block design with a 2×3×3 factorial arrangement, with two tomato hybrids (Netuno and San Vito), three doses of boron (H3BO3 - 0, 2, 4 g pit1)  and three calcium floral applications (no application; application every 7 days; and application every 14 days), totaling 18 treatments with four replications and 20 plants per plot.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Yield is correlated with NFP [ 61 ]. Hybrid 3 showed the highest NFP and one of the highest AFW values, resulting in the highest productivity among the treatments evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Yield is correlated with NFP [ 61 ]. Hybrid 3 showed the highest NFP and one of the highest AFW values, resulting in the highest productivity among the treatments evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…These predictions are greater than those of Valente et al [11], who selected ten progenies, managed them in the same area, under the same conditions used in the present study, and reported a mean yield of 763 g•plant −1 , or 847 kg.ha −1 . Plant breeding for yield and quality traits in fruits is complex due to the polygenic nature of these traits and the existence of genetic correlations among them [38][39][40][41].…”
Section: Selection Gains In Sacha-inchi Progeniesmentioning
confidence: 99%
“…Silva (2019), observou correlação positiva (r=0,95) entre a característica de número de frutos e produtividade total Diel et al (2019). verificou correlação positiva entre número de frutos por planta e produtividade total (r= 0,98) Sari et al (2017),.…”
unclassified